2015
DOI: 10.1016/j.addbeh.2015.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Friend or foe: Personal use and friends' use of protective behavioral strategies and spring break drinking

Abstract: The present study examined associations between use of protective behavioral strategies (PBS) by college students and their friends and drinking-related outcomes during Spring Break (SB). Moreover, this study examined the influence of friends’ own PBS use on participants’ PBS use during SB. Participants included college students (N = 694) and their nominated friends (N = 131) who were part of a larger study of SB drinking. Data were collected via web-based surveys that participants and friends took after SB, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
2
15
0
3
Order By: Relevance
“…Fourth, this study used the BYAACQ to measure daily negative consequences from drinking. Although the BYAACQ is an established measure and has been used to detect short-term alcohol-related problems in prior research (e.g., Lewis, Sheng, Geisner, Rhew, Patrick, & Lee, 2015; Pearson, D’Lima, & Kelley, 2013), this measure has not been standardized for use in a daily diary study. Although certain types of problems were detected on a daily level (50.9% of days involved at least one alcohol-related problem), a gold-standard measure is needed as many researchers move toward studying health behavior using daily or momentary assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study used the BYAACQ to measure daily negative consequences from drinking. Although the BYAACQ is an established measure and has been used to detect short-term alcohol-related problems in prior research (e.g., Lewis, Sheng, Geisner, Rhew, Patrick, & Lee, 2015; Pearson, D’Lima, & Kelley, 2013), this measure has not been standardized for use in a daily diary study. Although certain types of problems were detected on a daily level (50.9% of days involved at least one alcohol-related problem), a gold-standard measure is needed as many researchers move toward studying health behavior using daily or momentary assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, college students who employ serious harm reduction (SHR) and limiting/stopping (LS) protective behavioral strategies during drinking episodes actually drink in greater quantities and experience more alcohol‐related consequences. Moreover, friends’ use of SHR is also associated with increased alcohol consumption .…”
Section: Alcohol Misuse Research In College Environmentsmentioning
confidence: 99%
“…These efforts have demonstrated small effects on drinking quantity, frequency and experienced consequences, with minimal impact on high‐risk or heavy drinkers . Additionally, in certain cases these approaches have actually produced adverse consequences . It is our contention that alcohol prevention programming has been partially ineffective because researchers, policymakers and practitioners have overlooked the dynamically complex and ecological nature of drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional and longitudinal studies demonstrate that greater use of LS and MOD strategies are associated with less alcohol use and fewer consequences among college students (Frank, Thake, & Davis, 2012; Napper, Kenney, Lac, Lewis, & LaBrie, 2014; Pearson, 2013). However, three studies found that on days which participants reported above average increases of LS and SHR strategies (but not MOD), they also experienced greater drinking and consequences that day (Lewis et al, 2012, 2015; Pearson, D’Lima, & Kelley, 2013). While PBS are related to reduced alcohol use and consequences, young adults use of PBS is mixed (Nguyen, Walters, Wyatt, & DeJong, 2011; Ray, Stapleton, Turrisi, & Philion, 2012).…”
Section: Introductionmentioning
confidence: 99%